Investigation of Biliary Canal Variations as a Cause of Stone Formation in the Choledochal Canal - Medişoğlu, M. Sabri; Tuncay, Çolak; Ahmet, Yalnız; İsa, Çam; Mesut, Sezikli; Baltrak, Yusuf Atakan (Tropical Health and Medical Research, 2020)
The present study aimed to investigate if there is an association between the diameter of the choledochal duct and choledochal duct stone formation. The present study consisted of 79 patients who had endoscopic interventions and MRCP procedure with surgery history. Some followed due to disorders of the liver, gall bladder, and biliary tract and some of whom presented hepatobiliary complaints between 2017 and 2019. The choledochal duct diameter measured from MRCP images and choledochal duct stone had examined; the type classified according to Huang classification. Among the cases classified, 29 patients, was Huang Type A1, 27 patients were Huang Type A2, 16 patients were Huang Type A3, and seven patients were Huang Type A4. There was not any statistically significant association in terms of choledochal diameter regarding the types. Choledochal duct diameter was statistically higher in female patients than male patients (p<0.05). According to the age group, a statistically significant difference detected for choledochal duct stone formation; individuals over 45 years of age present an increase for choledochal duct stone (p<0.05). The choledochal duct diameter was found higher in female patients compared with male patients; stone formation has found increased in both gender over 45 years of age. It should consider before surgical procedures and radiological tests.